Studi Literatur: Kecemasan Saat Pandemi COVID-19 - Hardiyati Hardiyati; Efri Widianti; Taty Hernawaty (Politeknik Kesehatan Kemenkes Mamuju, 2020)
The coronavirus affects peoples' lives around the world. Social restriction policy can affect the psychosocial environment. Therefore restrictions and lockdown policies can increase a person's level of anxiety. This literature study identifies predisposing factors and reinforcing factors for anxiety feelings during the COVID-19 pandemic. The method used in writing this literature study is by searching the internet from the CINAHL database, EBSCOHost, Proquest, Pubmed, Google Scholar, and nursing books from 2010-2020 with the keyword anxiety facing Covid-19. Anxiety feeling during a pandemic can occur in a person due to predisposing factors including due to the COVID-19 pandemic, spending> 9 hours at home, excessive search for information online, more common in women, economy, having babies, married status, student status, learning environment, and internet network. Some actions that can reduce anxiety classified as reinforcing factors, namely emotional regulation, resilience, supportive intervention, religious coping, family support, limiting exposure to information media, and physical activity for sports. It can be explained that some factors that influence the occurrence of anxiety feelings are predisposing factors as well as preventive actions or those that can reduce anxiety during the COVID-19 pandemic classified as the reinforcing factor. Investigating influencing factors can help to understand the development and maintenance of anxiety feelings and to develop possible preventive measures and therapeutic interventions